Profitabilitas Dan Saluran Pemasaran Bibit Kubis: Studi Kasus Usaha Bibit Kubis H. Asep Di Desa Panggilingan Kecamatan Pasirwangi Kabupaten Garut - Imelia Putri; Muhamad Nu’man Adinasa; Najmi Alif Wardana; Parhan Muhamad Abdillah (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine: (1) Production costs of the H. Asep cabbage nursery in Callingan Village, Pasirwangi District, Garut Regency; (2) Profitability of the H. Asep cabbage plant nursery in Callingan Village, Pasirwangi District, Garut Regency; (3) The marketing channel for the H. Asep cabbage plant nursery in Callingan Village, Pasirwangi District, Garut Regency; (4) The amount of marketing margin for cabbage seedlings for each level of the institution. The method used is descriptive quantitative and data collection is done by data collection techniques with interviews and questionnaires as a guide. Respondents were determined by purposive sampling. The sample in this study is the owner of the business unit H. Asep Seeds. Data analysis methods used are cost analysis, profitability analysis, channel analysis and marketing efficiency. The results of this study are two patterns of marketing channels, namely (1) Producers ‒ final consumers, (2) Producers ‒ retailers ‒ final consumers. Based on the results of research on the business of H. Asep cabbage seedlings, the seeds can be said to be efficient with a price share of 73% to 81%.